Kerja Sama Korea Selatan-Indonesia dalam Akselerasi Mobil Listrik di Indonesia - El Shaddai, Sada Rhema; Wijayati, Hasna; Widhiyoga, Ganjar (Global Political Studies Journal, 2023)
Research has an urgency to analyze the implementation of cooperation between South Korea and Indonesia in accelerating electric cars in Indonesia in 2019-2021. The novelty of this research is the discussion of cooperation discussing government to government (G2G), government-to-business (G2B), and business-to-business (B2B). This research uses the theory of international cooperation discussing the implementation of cooperation through G2G in accelerating electric cars. Also, using international business theory discusses the implementation of cooperation through B2B in accelerating electric cars. With quantitative research methods, namely describing the topic of the problem and identifying problems, then analyzing with a predetermined theory and getting results according to research correlation. Data sources used through government publication data, journal articles, books, websites, and other supporting reports or publications. With the results of this study, the cooperation between South Korea and Indonesia can carry out 3 implementations. Implementation of government-to-government (G2G), government-to-business (G2B), and business-to-business (B2B) in 2019-2021. This study concludes that electric cars are technological innovations and the implementation of green growth policy. Impact for Indonesia and South Korea on economic and technological aspects. Keywords—Electric Vehicle, Foreign direct investment, Indonesia, International bilateral cooperation, South Korea